2020
DOI: 10.7150/jca.45676
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of the long noncoding RNA XIST suppresses glioma progression by upregulating miR-204-5p

Abstract: Background: Gliomas are the most prevalent primary malignant tumors of the central nervous system. Our previous study showed that miR-204-5p is a tumor suppressor gene in glioma. Bioinformatic analyses suggest that long noncoding RNA (lncRNA) X-inactive specific transcript (XIST) is a potential target gene of miR-204-5p. Methods: We analyzed the expression of XIST and miR-204-5p in glioma tissues and the correlation with glioma grade. A series of in vitro experiments were carried out to elucidate the role of X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…Their study reported that overexpression of miR-133a prevented glioma cell proliferation, metastasis and EMT by reducing the expression of SOX4 [ 159 ]. Consistently, other miRNAs, such as miR-429 [ 160 ], miR-210 [ 161 ], miR-92b [ 162 ] and miR-204-5p [ 163 ] may also modulates the expression of XIST in gliomas.…”
Section: Overview Of Long Non-coding Rnas In Glioblastomamentioning
confidence: 95%
“…Their study reported that overexpression of miR-133a prevented glioma cell proliferation, metastasis and EMT by reducing the expression of SOX4 [ 159 ]. Consistently, other miRNAs, such as miR-429 [ 160 ], miR-210 [ 161 ], miR-92b [ 162 ] and miR-204-5p [ 163 ] may also modulates the expression of XIST in gliomas.…”
Section: Overview Of Long Non-coding Rnas In Glioblastomamentioning
confidence: 95%
“…In 2020, four groups reported novel XIST-mediated ceRNETs that promote glioma progression, i.e., XIST/miR-133a/SOX4 ( Luo et al, 2020 ), XIST/miR-126/IRS1 ( Cheng et al, 2020 ), XIST/miR-204-5p/Bcl-2 ( Shen et al, 2020 ), and XIST/miR-329-3p/CREB1 ( Wang Y.P. et al, 2020 ).…”
Section: Examples Of Lncrna–mirna–mrna Cernets In Gliomamentioning
confidence: 99%
“…Furthermore, Cheng et al (2020) demonstrated that IRS1 promotes glioma progression by activating the PI3K/AKT pathway. Shen et al (2020) reported that XIST/miR-204-5p/Bcl-2 ceRNET regulates the proliferation, migration, invasion, and apoptosis of glioma cells. XIST can regulate a variety of apoptosis-related genes, including Bax, caspase 3, caspase 9, and Bcl-2; however, only Bcl-2 had been shown to be a direct target of miR-204-5p and was only tested in their study ( Shen et al, 2020 ).…”
Section: Examples Of Lncrna–mirna–mrna Cernets In Gliomamentioning
confidence: 99%
“…Moreover, miR-204-5p has been identified as another target of XIST in glioma cells. Interaction between XIST and miR-204-5p regulates expression of Bcl-2 (Shen et al, 2020). Figure 6 shows the interactions between XIST and miRNAs in glioma cells.…”
Section: Gliomamentioning
confidence: 99%